Statistics of highly heterogeneous flow fields confined to three-dimensional random porous media - Jin, Chunyu; Langston, Paul A.; Pavlovskaya, Galina E.; Hall, Mattew R.; Rigby, Sean P. (American Physical Society, 2016)
We present a strong relationship between the microstructural characteristics of, and the fluid velocity fields confined to, three-dimensional random porous materials. The relationship is revealed through simultaneously extracting correlation functions R-uu (r) of the spatial (Eulerian) velocity fields and microstructural two-point correlation functions S-2(r) of the random porous heterogeneous materials. This demonstrates that the effective physical transport properties depend on the characteristics of complex pore structure owing to the relationship between R-uu (r) and S-2(r) revealed in this study. Further, the mean excess plot was used to investigate the right tail of the streamwise velocity component that was found to obey light-tail distributions. Based on the mean excess plot, a generalized Pareto distribution can be used to approximate the positive streamwise velocity distribution.